Investigation of energy storage systems for electric and hybrid ships – part I - Lieu, Shi Ying (2017)
This final year report presents the different types of existing electrical energy storages. The purpose of the electrical energy storages is to store energy and help to offset the diesel usage on the vessels ship. With the different integration of energy storage, it will be more cost effective instead of using the conventional battery storage system which can help to enable the generator to maintain its efficiency. The report first presents the general requirement of the ships in the documentation and the system protection area. This allows us to understand the general guideline and rules that are needed to be comply in order to even build or install the system on the ships. After the general guideline of the ships, it continue on the areas of supercapacitor, flywheel, lead acid and lithium ion batteries. This include the areas of the fire safety, rules and protection that are required for installing the energy storage on the ship. In addition, there will be comparison among the four energy storage on the power rating, specific power energy, power density, discharging and charging time, cost and the efficiencies. The data and statistic are taken from the various results for the project by the commercial and research report. Lastly it will present the conclusion and recommendation for the integration of the different type of electrical energy storage and the importance of selection for the marine energy storage. In additional, it also highlight there is no mature rules and regulations for existing large scale battery installation on the ship. Lastly, this report may serve as a guideline and reference for the selection and design of the future marine energy storages in the future phase of the project.